2000
DOI: 10.1034/j.1600-0781.2000.160501.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of UV‐induced apoptosis

Abstract: Sunburn cells, single standing cells with typical morphologic features occurring in UV-exposed skin, have been recognized as keratinocytes undergoing apoptosis following UV irradiation. Induction of apoptosis following UV exposure appears to be a protective mechanism, getting rid off severely damaged cells that bear the risk of malignant transformation. UV-mediated apoptosis is a highly complex process in which different molecular pathways are involved. These include DNA damage, activation of the tumor suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
207
0
9

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(223 citation statements)
references
References 62 publications
(77 reference statements)
7
207
0
9
Order By: Relevance
“…In this way, a simple vicious circle can be established, the activity of which might be regulated in several ways. For instance, UV light can precipitate relapses in SLE patients (69), perhaps because of its capacity to induce apoptosis (70) and therefore generation of IFN␣-inducing material.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, a simple vicious circle can be established, the activity of which might be regulated in several ways. For instance, UV light can precipitate relapses in SLE patients (69), perhaps because of its capacity to induce apoptosis (70) and therefore generation of IFN␣-inducing material.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vitro and in vivo studies have clearly shown the role of p53 and WAF1/p21 and several other genes in UV response. 6,30,31 Studies have clearly shown that p53 mutation is an early event in UV skin carcinogenesis and the clonal expansion of p53-mutated cells leads to development of skin cancer. 4,5 In the present study, using "K5/ODC-transgenic mice," nontransgenic littermates, and SKH-1 hairless mice, we investigated the hypothesis that ODC plays a key role during UVB-mediated responses, including the develop- Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Besides its well-known advantages and its indispensable effects on human life, UV radiation, in particular the middle wavelength (UVB, range 290 -320 nm), can be a hazard to human health by inducing cancer, premature skin aging, immunosuppression, inflammation, and cell death (1)(2)(3)(4)(5). Accordingly, the incidence of UV-induced skin cancer is rapidly rising, accounting for Ͼ40% of all human cancers in the United States (6).…”
Section: Il-18mentioning
confidence: 99%